Edukasi Bijak Bermedsos: Membangun Literasi Digital untuk Santri Cerdas dan Beretika - Agusta, Gino Erman; Astriawati, Ningrum; Santosa, Prasetya Sigit; Widyanto, Handoyo (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The use of social media in the digital era has a significant impact, both positive and negative, especially for the younger generation such as students. This research aims to increase digital literacy and awareness of social media ethics among students of SMA IT Baitussalam through community service programs. This activity was carried out with an interactive socialization method that involved the creation of visual-based educational materials, discussions, and simulations. The material covers the benefits of social media, potential negative impacts, and guidelines for wise and responsible use. The results of the service show an increase in students' understanding in filtering information, preventing the spread of hoaxes, and using social media productively. Observation and interviews supported positive behavior change among participants. The conclusion of this activity shows that the interactive education approach is effective in building digital literacy, so that it can be applied in other educational environments to equip the young generation with ethical and responsible social media skills.